The effects of viral messages on netizens' emotions / Suhaila Sulaiman and Fadilah Puteh - Sulaiman, Suhaila; Puteh, Fadilah (2021)
2020 is the kick start for a new norm in life for all people worldwide. Covid-19 has triggered people to live in a digital world. Face-to-face communication has been replaced with video call and texting applications. E-commerce has overtaken physical business and shopping whereas online banking and services have become more convenient than walk-in banking services. Many government services have also provided online systems to reduce physical contact among clients. These changes force a major transition from manual to online services to occur especially in communication. One of the communication mediums is social media which connects people around the world and has become vital nowadays. Viral messages via social media are common nowadays. By sharing content among others and making it viral, there is little or no consideration for the involved parties' privacy issues, ethics, or thought of any possible damage or harm that such action may cause. The effects of viral content can be devastating to netizens' emotions as well. Emotion is one of the significant elements in sharing content via social media. It is one of the factors why we share or react to each social media content. Panger (2017) indicated that emotion plays an important role in social media and has been the subject of considerable research and media attention. Shahbudin (2020) said emotions that exist in an individual are classified as inner nature, which is, the feelings that exist through a person's response towards something. Jones et al. (2016) stated that articles with large comments were found to evoke high-arousal emotions, such as anger and happiness, paired with low-dominance emotions where people felt less in control, such as fear.